2011
DOI: 10.1007/s11596-011-0487-z
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b confers resistance of ovarian cancer cells to cisplatin by targeting pro-apoptotic Bcl-2 antagonist killer 1

Abstract: Chemotherapy is the preferred therapeutic approach for advanced ovarian cancer, but a successful long-term treatment is prevented by the development of drug resistance. Recent works have underlined the involvement of non-coding RNAs, microRNAs (miRNAs) in cancer development, with several conjectures regarding their possible involvement in the evolution of drug resistance. This study is to investigate the promoting effects and mechanism of miR-125b involved in the development of chemoresistance in ovarian cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…33,34 Furthermore, NF-κB, JUN and C-MYC have been linked to increased NRF2 activity in human cancer (including AML) 10,35 and NRF2 has been shown to transcriptionally regulate miR-125B in kidney epithelia cells in response to cisplatin-induced toxicity. 36 Taken together, it is likely that NRF2 has a central role in the complex network regulating miR-29B and miR-125B in human AML.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Furthermore, NF-κB, JUN and C-MYC have been linked to increased NRF2 activity in human cancer (including AML) 10,35 and NRF2 has been shown to transcriptionally regulate miR-125B in kidney epithelia cells in response to cisplatin-induced toxicity. 36 Taken together, it is likely that NRF2 has a central role in the complex network regulating miR-29B and miR-125B in human AML.…”
Section: Discussionmentioning
confidence: 99%
“…miR-125b is downregulated in resistant Ehrlich ascites tumor cells (25) and has been shown to increase the apoptotic response to cisplatin treatment in breast cells (26). Conversely, miR-125b has been found to be upregulated in Taxol-resistant cancer (9), doxorubicin-resistant Ewing sarcoma (27), cisplatin-resistant ovarian cancer (28) and AML (18) cells. In the present study, miR-125b upregulation was found to increase cell survival compared with that in the control cells, whereas miR-125b downregulation was observed to decrease cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that members of the B-cell lymphoma (Bcl)-2 family and other factors involved in apoptosis are important targets of miR-125. Numerous proteins have been shown to affect apoptosis, including anti-apoptotic members of the Bcl-2 family, such as Bcl-w (30), Bcl-2 (31), myeloid cell leukemia sequence 1 (30,32) and Bcl-2-antagonist/killer (Bak)-1 (9,28,30,32), acting as the Bcl-2 homologous antagonist, and pro-apoptotic targets, including P53 (33), tumor protein p53-inducible nuclear protein 1 (TP53INP1) (34), tumor necrosis factor α-induced protein 3 (35) and p38α (36). High miR-125 expression has been shown to downregulate Bak-1 and TP53INP1, and consequently protects cells from apoptosis and promotes tumorigenesis (37).…”
Section: Discussionmentioning
confidence: 99%
“…The negative control contained <0.1% dimethylsulfoxide without CB (0 mM). After 24, 48, 72, and 96 h, 10 mL CCK-8 reagent (CCK-8 assay kit for measuring cell proliferation and cytotoxicity; Beyotime Institute of Biotechnology, Haimen, China) was added to the cells and incubated for 2 h. Absorbance was measured at 450 nm as optical density (OD) values using a KHB ST-360 microplate reader (Kehua Laboratory System Co., Ltd., Shanghai, China) (Espindola et al, 2000;White et al, 2001;Kong et al, 2011). The percentages of cell viability were calculated in each group using the following formula: Cell viability (%) = (OD experimental -OD blank / OD control -OD blank ) x 100%.…”
Section: Cck-8 Assaymentioning
confidence: 99%